A Boron 2‐(2′‐pyridyl) Imidazole Fluorescence Probe for Bovine Serum Albumin: Discrimination over Other Proteins and Identification of Its Denaturation. (31st July 2017) - Liu, Chunlin; Yang, Wei; Du, Jinya; Shen, Ping; Yang, Changying
Abstract: Boron 2‐(2′‐pyridyl) imidazole complex (BOPIM) derivatives, BOPIM‐1 and BOPIM‐2, involving twisted intra‐molecular charge transfer (TICT) characteristic, were investigated to probe bovine serum albumin (BSA). BOPIM‐1 was demonstrated to be an efficient fluorescence probe to discriminate BSA from other proteins including human serum albumin (HSA). The encapsulation of BOPIM‐1 in the hydrophobic subdomain IIA of BSA inhibited the TICT state and resulted in 70‐fold emission enhancement of BOPIM‐1. Besides, it was found that BOPIM‐1 could distinguish denatured BSA from the native, due to the difference of 15 nm emission wavelength at least. The denaturation of BSA leads to the exposure of binding sites and resulted in an increase in the accessibility of the fluorophore to the BSA cavity, which made a great contribution to the further restraint of TICT state of BOPIM‐1. The tracking of BSA denaturizing process was easily achieved, through the change of BOPIM‐1 emission wavelength from 485 to 465 nm. Thus, a promising pharmacological dual‐functional probe was provided for both the selective recognization of BSA and the identification of denatured BSA from the native. Abstract : A dual‐functional fluorescence probe BOPIM‐1 is for both sensitively discriminating bovine serum albumin (BSA) from other proteins and detecting denatured BSA.